Fibroblast growth factor inducible 14 (Fn14) is expressed in the lower genital tract and may play a role in amplifying inflammation during infection - Han, Eugene S. (2009)
TNF-like weak inducer of apoptosis (TWEAK) is a member of the tumor necrosis factor (TNF) cytokine superfamily which regulates a number of cellular responses, including inflammation and proliferation. TWEAK is primarily secreted by phagocytic cells and its receptor, fibroblast growth factor-inducible 14 (Fn14), is expressed on non-lymphoid cells, including epithelial, endothelial and mesenchymal cells. The TWEAK/Fn14 pathway is highly conserved from an evolutionary standpoint, and has been shown to play a role in tissue regeneration and inflammation in the liver, kidney, lung and skeletal muscle. We hypothesized that TWEAK/Fn14 might have a physiological role in regulating infection-induced inflammation in the lower female genital tract. To test this hypothesis, we examined expression of the receptor Fn14 in relevant cells and tissue. Receptor function was tested by treating cells with recombinant TWEAK, with and without other known pro-inflammatory stimuli. Flow cytometric analysis of vaginal and cervical epithelial cells revealed that Fn14 was highly expressed at the cell surface. We also detected both Fn14 and TWEAK in whole cervical tissue by RT-PCR. Treatment of vaginal and cervical epithelial cells with recombinant TWEAK led to a weak induction of the chemokine IL-8. However, TWEAK potentiated the effects of IL-1ß, the TLR2 ligand Pam(3)CysSK(4), and live Neisseria gonorrhoeae in a synergistic manner. These data reveal a novel pathway for regulation of microbial-induced inflammation in the female reproductive tract and suggest that interference with the TWEAK/Fn14 pathway might be an approach to abrogate excessive infection-induced inflammation caused by sexually transmitted pathogens.